King Arthur : opposing viewpoints - d (San Diego : Greenhaven, 1992)
Examines the conflicting evidence about the existence and historical basis of the legendary British king.
Includes bibliographical references (p. 107-108) and index.
Booklist.
School Library Journal.
Wilson's Junior High School.
6.9
5-8
Keywords: Arthur, -- King -- Juvenile literature; Arthur, -- King; Arthur, -- King; Arthurian romances -- Sources -- Juvenile literature; Britons -- Kings and rulers -- Biography -- Juvenile literature; Kings, queens, rulers, etc; Kings and rulers; Great Britain -- Antiquities, Celtic -- Juvenile literature; Great Britain -- History -- To 1066 -- Juvenile literature; Great Britain -- History -- To 1066.; Great Britain -- History -- 0-1066.